MR imaging-guided intravenous thrombolysis in posterior cerebral artery stroke - Förster, Alex; Gass, Achim; Kern, Rolf; Wolf, Marc; Hennerici, Michael G.; Szabo, Kristina (American journal of neuroradiology, 2011)
SUMMARY: PCA stroke was under-represented in or excluded from the clinical trials examining thrombolysis based on the PWI-DWI mismatch concept. We present 6 patients with PCA stroke treated with thrombolysis in an extended time window by using MR imaging criteria. Symptoms included aphasia, sensorimotor hemiparesis, hemineglect, and homonymous hemianopia. Initial MR imaging demonstrated circumscribed ischemic lesions in the thalamus or hippocampus; MR angiography showed PCA occlusion with corresponding hypoperfusion. Follow-up MR imaging showed partial/complete recanalization in 4 patients with minor infarction growth, while in 1 patient, PCA occlusion persisted, resulting in a large PCA infarction. Three patients improved within 2 hours; at discharge, homonymous hemianopia had resolved in 3 patients. At 3-month follow-up, 4 patients had an mRS score of 0 or 1. These results support the approach to treat patients with PCA stroke with thrombolysis based on the mismatch concept. Because rehabilitation options for hemianopia are limited, thrombolysis may enhance the chance of a favorable outcome.
Gesehen am 15.05.2023